Analisis Usahatani Wortel (Daucus carota L) Organik dan Non Organik (Studi Kasus pada Pusat Pelatihan Pertanian dan Perdesaan Swadaya (P4S) Eka Setia Lestari, Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan) - SUPUTRA, GDE NUSHA; WIDYANTARA, I WAYAN; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p01, 2018)
The Organic and Non Organic Carrot Farming Analysis (Case Study on P4S Eka Setia Lestari, Bangli Village, Baturiti Sub-District, of Tabanan Regency) The objectives of the research are to determine the differences of income of the organic and non organic carrot farming. The second objective is to find out the constraints faced by the organic and non organic farmers.The research was conducted in Bangli Village, Baturiti Sub-District, Tabanan Regency. Determination of the location is done purposively because Eka Setia Lestari already has organic certificate and recognized by the LeSos Organic Institute. The respondents were farmers who planted carrots during the planting season of September - December 2015 at P4S Eka Setia Lestari with the number of 24 people. Determination of respondents of the research was conducted by census method. The analysis used was farm income analysis, Mann Whitney test, and descriptive analysis. The results showed that the organic carrot income was Rp 7,646,446.67 and non-organic carrot income of Rp 6,191,229.06. Based on the results of Mann Whitney test, it was obtained significant differences between the incomes of farmers who grew organic and non-organic carrots . The constraint faced by the organic carrot farmers is that carrots are more susceptible to pests and diseases attacks while the constraint experienced by the non-organic carrot farmers is the price fluctuations in the sale of carrots in the market.